PENGARUH HANDOUT BERGAMBAR DISERTAI PETA KONSEP DALAM MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION TERHADAP KOMPETENSI BELAJAR SISWA KELAS X SEMESTER II SMA KARTIKA 1-5 PADANG TAHUN AJARAN 2013/2014 - Sasriyanti, Yuri - (Pendidikan Biologi, 2014)
The least of biology learning media at SMA Kartika 1-5 Padang cause the studentsâ low learning out cont of biology. The teacher should choose good method and interesting media by using picture Handout with map concept in Cooperative Learning Model Type Student Team Achievement Division (STAD). This is experiment research with Randomized Control Group Posttest Only Design. The population of the research is all of the students class X SMA Kartika 1-5 Padang which are registered at II semester year 2013/2014. Take of sampling uses Purposive Cluster Sampling. The result of this technique is got experiment class and control class includes that X4 and X2. The result of the research is got score of experiment class 77.85 and control class 67.35. Average score is about affective, cognitive, and Psychomotor for X4 73% and X2 52%. This case can be concluded that picture Handout with map concept in cooperative learning model type STAD give effect toward the studentsâ biology score at class X SMA Kartika 1-5 Padang year 2013/2014.